Answer: x=−3
Step-by-step explanation: Let's solve your equation step-by-step.
2
3
(3x+9)=−2(2x+6)
Step 1: Simplify both sides of the equation.
2
3
(3x+9)=−2(2x+6)
(
2
3
)(3x)+(
2
3
)(9)=(−2)(2x)+(−2)(6)(Distribute)
2x+6=−4x+−12
2x+6=−4x−12
Step 2: Add 4x to both sides.
2x+6+4x=−4x−12+4x
6x+6=−12
Step 3: Subtract 6 from both sides.
6x+6−6=−12−6
6x=−18
Step 4: Divide both sides by 6.
6x
6
=
−18
6
x=−3
Answer:
Yes it is
Step-by-step explanation:
Simplify the expression:
7 - 5x - (3 + 5x)
Operate the parentheses. Each term changes its signs because the minus sign represents a -1:
7 - 5x - (3 + 5x) = 7 - 5x - 3 - 5x
Collect like terms:
7 - 5x - (3 + 5x) = 7 - 3 -5x - 5x
Simplify:
7 - 5x - (3 + 5x) = 4 - 10x
Answer: 4 - 10x
It is 1/10 times the value represented in the 2 in 423.
It is 10 times the value represented in the 2 in 72
1 hundred, 8 tens, and 2 ones